1970
DOI: 10.2136/sssaj1970.03615995003400030020x
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Distribution of Organic Chemicals in Solution and Adsorbed as a Function of Position and Time for Various Chemical and Soil Properties

Abstract: Equations were developed to describe the mass transfer of organic chemicals through soil and evaluated for various soil conditions. Movement due to diffusion was assumed to be negligible. The model assumed the relationship ∂S/∂t = α(Kc − S) where S is the adsorbed concentration [mass per total volume], c is solution concentration [mass per total volume], t is time, and K and α are constants. The model also considered the effect of applying various amounts of chemical to the soil surface and allowed for a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…To account for heavy‐tailed behavior, modified models of the advection‐dispersion equation (ADE), with additional terms that account for longer timescales of transport, have been developed [e.g., Haley et al , 1991; Berkowitz , 2002]. The primary conceptual models for these additional transport processes are (1) the inclusion of additional diffusion processes in the mobile domain as a function of heterogeneity within the experimental media [e.g., Berkowitz et al , 2006; Dentz and Tartakovsky , 2006; Hill et al , 2006], or (2) kinetic exchange between mobile and immobile zones within porous media (e.g., first‐order, spherical, or multimodal) [ Lapidus and Amundson , 1952; Oddson et al , 1970; van Genuchten et al , 1974]. Haggerty et al [2000] note that the representation of the exchange process can take many forms, each of which will result in different simulated residence time distributions of tracer in the system.…”
Section: Introductionmentioning
confidence: 99%
“…To account for heavy‐tailed behavior, modified models of the advection‐dispersion equation (ADE), with additional terms that account for longer timescales of transport, have been developed [e.g., Haley et al , 1991; Berkowitz , 2002]. The primary conceptual models for these additional transport processes are (1) the inclusion of additional diffusion processes in the mobile domain as a function of heterogeneity within the experimental media [e.g., Berkowitz et al , 2006; Dentz and Tartakovsky , 2006; Hill et al , 2006], or (2) kinetic exchange between mobile and immobile zones within porous media (e.g., first‐order, spherical, or multimodal) [ Lapidus and Amundson , 1952; Oddson et al , 1970; van Genuchten et al , 1974]. Haggerty et al [2000] note that the representation of the exchange process can take many forms, each of which will result in different simulated residence time distributions of tracer in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the initial values for the soil P variables are all set to zero. Table ( (Lee et al, 1989) (3): SWAT model (Arnold et al, 1998), (4): HSPF model (Donigian et al, 1984), (5) : Oddson, et al, (1970). On running the hydrological model (SHETRAN) on the catchment, a significant water depth (>0.005m) resulted in elements 2, 4, and 1 while the remaining two elements (3, and 5) recorded a practical zero water depth (<0.005m).…”
Section: An Example Of the Gopc Applicationmentioning
confidence: 99%
“…This method can be used for determining the spatial moments of solute concentration in homogeneous columns. In practical applications other simplified models such as one-site models (Bahr and Rubin, 1987;Lapidus and Amundson, 1952;Oddson et al, 1970;Rao et al, 1980), two-site models (Cameron and Klute, 1977;Selim et al, 1976, andNkedi-Kizza et al, 1984) or multiple-rate models (Haggerty and Gorelick, 1995) are used. Rao et al (1980) also showed the failure of one-site models manifested as an apparent time dependence of the exchange rate coefficient.…”
Section: Introductionmentioning
confidence: 99%